Boyd's film diffusion model for water contaminant adsorption: Time for an upgrade? - Chu K.H.; Hashim M.A.; Hayder G. (Elsevier B.V., 2025)
The Boyd film diffusion model is widely used in liquid phase adsorption studies for its mathematical simplicity and straightforward data analysis. However, a lack of awareness regarding its restrictive assumptions has led to widespread misuse. The Boyd model assumes film diffusion as the rate-controlling mechanism and rests on two additional pivotal assumptions: adsorption occurs under infinite bath conditions and follows a linear equilibrium relationship. This study examines the recurrent breaches of these assumptions across a growing body of research on water contaminant adsorption. Nearly all kinetic data have been derived from finite bath experiments governed by nonlinear isotherms, which directly contradict the Boyd model's assumptions. Consequently, applying the Boyd model to such data can yield misleading results and interpretations. To address these challenges, alternative models tailored for finite bath conditions and capable of accommodating both linear and nonlinear isotherms should be considered. These models offer more accurate insights into adsorption kinetics under realistic experimental settings. While the Boyd model remains valuable under specific conditions, its stringent assumptions restrict its broader applicability. Researchers should critically assess the validity of these assumptions and explore alternative models when analyzing liquid phase adsorption kinetics to ensure robust and reliable results. ? 2024 Elsevier B.V.